Comparative Risk of Hospitalized Bleeding of P2Y12 Inhibitors for Secondary Prophylaxis in Acute Coronary Syndrome After Percutaneous Coronary Intervention. Issue 2 (28th December 2022) - Kumar, Arun; Lutsey, Pamela L.; St. Peter, Wendy L.; Schommer, Jon C.; Van't Hof, Jeremy R.; Rajpurohit, Abhijeet; Farley, Joel F.
Abstract : In closely monitored randomized controlled trials (RCTs), newer P2Y12 agents (ticagrelor and prasugrel) reduced cardiovascular outcomes compared with clopidogrel following percutaneous coronary intervention (PCI) in acute coronary syndrome. However, these RCTs indicated a higher bleeding risk with these newer agents. This study evaluated the comparative safety of each P2Y12 inhibitor on hospitalizations due to major bleeding in a real‐world population. This retrospective, propensity score‐matched (PSM) cohort study utilized the IBM MarketScan database over 6 years (2013–2018) to identify incident users of P2Y12 inhibitors with age ≥18 years. The primary safety outcome was hospitalization due to any major bleeding event including gastrointestinal, intracranial, and other serious forms of bleeding. In pairwise comparisons using Cox‐proportional hazards models, ticagrelor, prasugrel, and clopidogrel users were compared for the primary safety outcome at 30, 90, and 180 days following the first prescription of P2Y12 inhibitor after PCI. There were 21, 719 (ticagrelor vs. clopidogrel), 11, 513 (prasugrel vs. clopidogrel), and 11, 065 (prasugrel vs. ticagrelor) PSM pairs. Overall, the risk of major bleeding was similar for all P2Y12 inhibitors. Hospitalization for major bleeding was generally lower among ticagrelor users vs. clopidogrel and higher among prasugrel users compared with clopidogrel. Importantly, a 66% higher risk of major bleeding at 90 days is suggested with prasugrel compared with clopidogrel (hazard ratio 1.66; 95% confidence interval, 1.11–2.48). This study indicated a higher short‐term bleeding risk with prasugrel compared with clopidogrel, which concurs with the results of RCTs.